Faktor Risiko Kejadian Katarak - Motris Pamungkas; Yeni Mahwati; Suparni Suparni; Siti Sugih Hartiningsih; Weni Tusrini (Jurnal Sehat Masada, 2024)
Cataract is one of the leading causes of blindness in the world and in Indonesia. The prevalence of blindness due to cataracts increases annually by 0.1% of the total Indonesian population. Cataracts are caused by several risk factors. Based on this, early prevention efforts are needed to reduce the risk factors for cataract blindness. The purpose of this study was to determine the description of risk factors for cataract incidence based on the epidemiological triad, determine the relationship and magnitude of risk factors for cataract incidence. This type of research uses a literature review method of 16 journals consisting of 12 national journals and 4 international journals that discuss cataract risk factors. The results showed that risk factors were significantly associated with a p value of <0.05 with cataract incidence. Host risk factors are age â‰¥60 years, female gender, low education level, non-white race, genetic history (family cataract, diabetes mellitus, hypertension), and smoking habit. Based on agent exposure to ultraviolet light, and lack of antioxidant consumption are more at risk for cataract incidence. Then based on the environment, risk factors consist of climate, work outside the building, and low income levels. In conclusion, age, gender, education, race, genetic history (family cataract, diabetes mellitus, hypertension), smoking habit, ultraviolet light exposure, lack of antioxidant consumption, climate, occupation, and income level are significantly related and at risk for cataract incidence.